L’écriture dans Le Lambeau de Philippe Lançon est-elle témoignage pharmakon ou salut existentiel ? - Urbanik-Rizk, Annie (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
On January 7th 2015, Philippe Lançon, a journalist at Libération and at Charlie Hebdoattends the newspaper’s premises, when the islamist terrorists attack. The killers’bulletstear his jaws off, severely injure his arms, make his existence capsize, but he survives. In hisnovel Le Lambeau, he tells the story of a mental as well as physical reconstruction, sketchingthe chronology of his days in various hospitals, depicting the visitors who make his daysbrighter and the varied shades of his consciousness.Is his writing, a mere testimony of a tragical experiment, the chronicles of a journalistwho witnesses how one comes back to life? Or is it a pharmakon, a poison within a remedy,which puts back to life things past and gone, as a way of healing? Or shall we give a spiritualsignificance to this writing, so haunted by Proust that it parodies his style and showsliterature as a means of salvation?